2009
DOI: 10.1007/s11418-009-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Difference of ITS sequences of Akebia plants growing in various parts of Japan

Abstract: The stem of Akebia plant, "Mokutsu", is a crude diuretic and antiphlogistic drug.Japanese products prepared from wild Akebia plants covers most of the Mokutsu market. Two Akebia plants, Akebia quinata Decaisne (Aq) and A. trifoliata Koidzumi (At) of Lardizabalaceae, are standardized as "Mokutsu" in Japanese pharmacopoeia. These 2 Akebia plants along with A. × pentaphylla Makino (Ap), which is considered a hybrid with the morphology of Aq and At, can be distinguished by DNA sequence analysis of internal transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The stem of this plant is traditionally used to activate blood circulation and inhibit inflammation in Japan and China. The dried young leaves of this plant can be used as a tea alternative, and the fruits are used to make sweeteners, juice, and fruit vinegar. , A. trifoliata var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stem of this plant is traditionally used to activate blood circulation and inhibit inflammation in Japan and China. The dried young leaves of this plant can be used as a tea alternative, and the fruits are used to make sweeteners, juice, and fruit vinegar. , A. trifoliata var.…”
Section: Introductionmentioning
confidence: 99%
“…The dried young leaves of this plant can be used as a tea alternative, and the fruits are used to make sweeteners, juice, and fruit vinegar. 2,3 A. trifoliata var. australis seed oil (ASO) was used as an edible oil in southern China during the period of shortage of edible oil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Molecular markers based on conserved DNA elements, including maternal chloroplast and biparental nuclear genomic markers, have been widely employed to investigate population genetic diversity. In this study, a previously reported chloroplast gene ( rps16 ) and a nuclear DNA marker (ITS) were used to determine the genetic diversity of the A. trifoliata population [ 35 , 36 ]. We first checked 22 and 75 haplotypes from 59 to 88 polymorphic sites in the rps16 and ITS sequences, respectively (Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total genomic DNA was extracted according to the previously published CTAB method. The rps16 chloroplast gene and ITS were selected as maternally and biparentally inherited molecular markers, respectively [ 35 , 36 ]. The corresponding primers were synthesized and then subjected to polymerase chain reaction (PCR) according to a previously described reaction system and program [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…× pentaphylla has five leaflets with slightly wavy edges and pale purple male and female flowers (Makino, 1989 ; Satake et al, 1997 ). However, some naturally occurring individuals of this species exhibit boundary morphologies (Kitaoka et al, 2009 ). Two varieties of this species have been published: Akebia × pentaphylla “Pikapika” is a variety with white young leaflets and green branches; Akebia × pentaphylla “Purple Incense” has fragrant dark purple flowers and exceptionally large fruit.…”
Section: Botanical and Ecological Characteristics Of The Ak...mentioning
confidence: 99%